MicroRNA Signatures Associated with Basal Cell Carcinoma Subtypes - Suzanne Fastner; Hafeez Rahman; Jose Gutierrez; Nathan Shen; Scott R. Florell; Abigail Florell; Chris J. Stubben; Kenneth M. Boucher; Dekker C. Deacon; Robert L. Judson-Torres; Douglas Grossman (Elsevier, 2024)
Basal cell carcinoma (BCC) is classified histologically into subtypes that determine treatment decisions. MicroRNAs (miRs) are short noncoding RNAs that may serve as diagnostic biomarkers. We investigated if particular miRs could distinguish BCC subtypes. We sequenced miRs from 55 archival BCC and 9 control skin specimens and then validated these miRs by qRT-PCR assay on a second BCC cohort (18 superficial, 16 nodular, 15 infiltrative) and control skin (n = 12). Expression values for individual miRs were normalized to miR-16-5p, which was the least variant among the control skin and BCC samples. We found that (i) miR-383-5p and miR-145-5p are downregulated in all BCC subtypes compared with control skin, (ii) miR-181c-5p is downregulated in superficial compared with invasive (nodular/infiltrative) BCC, and (iii) miR-22-5p and miR-708-5p are upregulated in infiltrative compared with superficial/nodular BCC and miR-30c-5p is downregulated in infiltrative compared with nodular BCC. Receiver operating characteristic analysis demonstrated excellent capacity of these miRs to discriminate between BCC and control skin (area under the curve, 0.94-0.98), whereas the capacity to discriminate between superficial and invasive subtypes was less robust (area under the curve, 0.7-0.8). Future prospective studies may determine the utility of these miRs as diagnostic biomarkers to guide biopsy and treatment of BCC.